(untitled) (Journal of Philosophy, Culture and Political Science, 2016)
In this article the authors examine the issue of tolerance in close connection with the idea of tolerance. The genesis of the idea of tolerance goes back to the ancient history and formed much earlier than the idea of tolerance. It goes to the ancient history of Greek, Chinese and Indian culture. One of the important aims of Science’s culture is to find out the role of spiritual moral factors in the formation of tolerance. Studying of this aspect reveals the social and spiritual factors affecting formation of tolerance and human’s behavior in society.